2010
DOI: 10.1088/0004-637x/715/2/743
|View full text |Cite
|
Sign up to set email alerts
|

HUBBLE RESIDUALS OF NEARBY TYPE Ia SUPERNOVAE ARE CORRELATED WITH HOST GALAXY MASSES

Abstract: From Sloan Digital Sky Survey u' g' r' i' z' imaging, we estimate the stellar masses of the host galaxies of 70 low redshift SN Ia (0.015 < z < 0.08) from the hosts' absolute luminosities and mass-to-light ratios. These nearby SN were discovered largely by searches targeting luminous galaxies, and we find that their host galaxies are substantially more massive than the hosts of SN discovered by the flux-limited Supernova Legacy Survey. Testing four separate light curve fitters, we detect ∼2.5σ correlations of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
420
4
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(464 citation statements)
references
References 81 publications
(155 reference statements)
39
420
4
1
Order By: Relevance
“…There is no appreciable difference in DM 0 between the Hard Classification Model and the Soft Classification Model. In accordance with previous results (Kelly et al 2010;Sullivan et al 2010;Campbell et al 2016), we find that SNe Ia in more massive galaxies are intrinsically brighter, with our posterior estimate of the magnitude difference being D = - M 0.055 0.022 0 . However, the size of the effect in our study is smaller than previously reported.…”
Section: Including Corrections For Host Galaxy Masssupporting
confidence: 93%
See 1 more Smart Citation
“…There is no appreciable difference in DM 0 between the Hard Classification Model and the Soft Classification Model. In accordance with previous results (Kelly et al 2010;Sullivan et al 2010;Campbell et al 2016), we find that SNe Ia in more massive galaxies are intrinsically brighter, with our posterior estimate of the magnitude difference being D = - M 0.055 0.022 0 . However, the size of the effect in our study is smaller than previously reported.…”
Section: Including Corrections For Host Galaxy Masssupporting
confidence: 93%
“…) host brighter SNe Ia, with their average absolute magnitude being of order ∼0.1 mag smaller than in less massive hosts (Kelly et al 2010;Sullivan et al 2010;Campbell et al 2016). This could be a reflection of dust, age, and/or metallicity in the progenitor systems (Childress et al 2013b).…”
Section: Dependence On Host Galaxy Massmentioning
confidence: 92%
“…This breadth of host conditions provides a laboratory for the investigation of the evolution of SNe Ia as distance indicators. Recently such an effect was found and calibrated in the form of a modest, 0.03 mag dex −1 relationship between host galaxy stellar mass (a likely tracer of metallicity) and calibrated SN Ia magnitude (Kelly et al 2010;Lampeitl et al 2010;Sullivan et al 2010;see Hicken et al [2009b] for an analysis with host morphology and Hayden et al [2012] for an analysis that incorporates star formation rate in an attempt to isolate metallicity). At the level of precision enabled by current surveys, it is necessary to correct for this effect , but the uncertainty in the correction is not a limiting systematic.…”
Section: Systematic Uncertainties and Strategies For Ameliorationmentioning
confidence: 99%
“…Furthermore, even for SN Ia, which arise from the thermonuclear explosion of a white dwarf at or near the Chandraskhar mass limit in a binary system, host galaxy studies have uncovered trends for SN Ia luminosity with host galaxy morphology (e.g., Hamuy et al 1996) and mass (e.g., Kelly et al 2010;Sullivan et al 2010), where more luminous SN Ia tend to be in more luminous and (assuming the luminosity-metallicity relationship for galaxies) metalrich galaxies, which is consistent with measured metallicity studies (Gallagher et al 2008). However, for SN Ia with their long delay times (200 Million yrs to a few Gigayears, e.g., Maoz 2010) and the associated large offsets between birth and explosion sites, it is not clear whether measuring the gas-phase metallicity (which reflects that of the currently starforming gas) at the SN position really reflects the natal metallicity of the old progenitor (Bravo & Badenes 2011).…”
Section: Sn and Grb Host Metallicity Measurements As A Rapidly Expandmentioning
confidence: 99%